Proc. 29th Annual Conference of the International Group for Lean Construction (IGLC) 2021
DOI: 10.24928/2021/0219
|View full text |Cite
|
Sign up to set email alerts
|

Choosing by Advantages for the Selection of a New Member of the Project Team

Abstract: The construction industry works through projects; each project needs people who make its realization possible, and these people relate to each other, forming work teams. Thus, there is an important relationship between the projects and the team members of a construction project, who must be selected based on competencies that allow them to satisfactorily perform their role in the project and thus contribute to the project's success. This research aims to provide a systematic approach while also providing decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…["I hope he/she participates in the interview…, I perceived a lack of interest"]. In addition, taking as a reference a previous documented experience ( Paucar-Espinoza et al, 2021), it was shown that the face-to-face use of the CBA method was more beneficial than its virtual use. Social aspects play an important role in the decision-making process (Martínez et al, 2016), even more so if the objective is to minimize bias.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…["I hope he/she participates in the interview…, I perceived a lack of interest"]. In addition, taking as a reference a previous documented experience ( Paucar-Espinoza et al, 2021), it was shown that the face-to-face use of the CBA method was more beneficial than its virtual use. Social aspects play an important role in the decision-making process (Martínez et al, 2016), even more so if the objective is to minimize bias.…”
Section: Discussionmentioning
confidence: 96%
“…Suhr (1999) developed CBA, and it has been adopted in the Lean Construction community mainly for design and construction decisions. For example, Paucar-Espinoza et al (2021) used CBA for selecting a new team member; however, their study did not consider bias mitigation strategies.…”
Section: Choosing By Advantagesmentioning
confidence: 99%
See 2 more Smart Citations